Compliance With Institutional Antimicrobial Dosing Guidelines in Patients Receiving Continuous Venovenous Hemodialysis. (August 2015) - Fedorenko, Marianna; Lam, Simon W.; Harinstein, Lisa M.; Neuner, Elizabeth A.; Demirjian, Sevag; Bauer, Seth R.
Objective: Describe the rate of compliance with institutional antimicrobial dosing guidelines in patients on concomitant continuous venovenous hemodialysis (CVVHD). Methods: This single-center retrospective chart review evaluated adult patients receiving concomitant intravenous antimicrobials and CVVHD for at least 24 hours over a 2-month period. Results: A total of 42 patients, 76 antimicrobial courses, and 208 study days (24 hours of concomitant therapy) were evaluated. Overall, antimicrobials were dosed according to the institutional guidelines on 162 (78%) of 208 study days. All nonconcordant doses were below recommendations. The recommended dose was never received prior to antibiotic or CVVHD discontinuation in 22% of the cases. In cases where antimicrobials were initiated when the patient was already on CVVHD, 74% of the initial doses met guideline criteria. Pharmacist recommendation was associated with increased dosing compliance (94% vs 73% of study days, P = .001). During transition from CVVHD to intermittent hemodialysis (IHD), only 62% of antimicrobial doses were decreased by the first IHD day. Conclusions: Antimicrobial dosing in patients on CVVHD was below institutional guideline recommendations in many cases. Pharmacist recommendation was associated with compliance. Centers should evaluate their own compliance rate with institutional guideline recommendations for CVVHD and implement initiatives to improve dosing practices.